2010
DOI: 10.1007/s13187-009-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Variables Leading to Burnout in Cancer Physicians

Abstract: Background. Although communication skills training programs have been recommended

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
16
0
2
Order By: Relevance
“…Two (Bragard et al, ; Taylor et al, ) showed just EE. Seven (Balbay et al, ; Bar‐Sela et al, ; Bragard et al, ; Demirci et al, ; Leung & Rioseco, ; Liakopoulou et al, ; Probst et al, ) did not provide specific data on the prevalence of high subscale scores. However, apart from Leung and Rioseco (), six of these did provide mean scores for all three of the subscales (EE, DP, low PA), see Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two (Bragard et al, ; Taylor et al, ) showed just EE. Seven (Balbay et al, ; Bar‐Sela et al, ; Bragard et al, ; Demirci et al, ; Leung & Rioseco, ; Liakopoulou et al, ; Probst et al, ) did not provide specific data on the prevalence of high subscale scores. However, apart from Leung and Rioseco (), six of these did provide mean scores for all three of the subscales (EE, DP, low PA), see Table .…”
Section: Resultsmentioning
confidence: 99%
“…Bragard et al () found that higher burnout scores on the subscales of emotional exhaustion and depersonalisation were associated with an increase in psychosomatic disorders and anxiolytic usage. While the findings of the study are limited in their generalisability due to only being conducted in France and applicable to oncologist residents, all applicable oncology residents in the nation were invited to participate, with a response rate of 60%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations